Studying The Effect of The Manufacturing Process of Heusler Compounds Co2MnZ (Z=Ga, Ge, Si) on its Crystal Order and Magnetic Properties - Hamayoon Rahmani; Mohammad Jawad Hamta; Ibrahim Tawana; Hussain Aziz (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
The effect of different manufacturing processes, such as arc melting, mechanical alloying, and baking, on the crystalline and magnetic behavior of Co2MnSi, Co2MnGa, and Co2MnGe compounds was investigated. Samples of Co2MnSi, Co2MnGe, and Co2MnGa compounds were produced using the arc melting method and the effect of mechanical alloying and annealing processes on the manufactured products was investigated. The results showed that the use of different processes during manufacturing leads to different crystalline and magnetic behaviors of the sample. One of these cases is the correlation of the crystal order with the lattice parameter size in the produced samples and its effect on reducing the saturation magnetization compared to Slater and Pauling's prediction. Also, the change of order induced by the mechanical alloying process in the production of Co2MnSi composition has led to a drop of about 14% in saturation magnetization. The coercivity in the sample produced by arc melting and mechanical alloying in Co2MnGe composition is lower than the expected value, which was attributed to the low magnetic anisotropy of the sample due to the small size of the crystals in this sample, which is compensated in the cooking process. For example, performing the grinding process before baking leads to a change in the crystal order and, consequently, to a decrease in the saturation magnetization of the sample. The final baking increases the size of the crystals and reduces the strain. The sample obtained from grinding after arc melting had more coercivity than the other two samples due to having smaller crystals.